ANALISIS ILUSI NUMERASI TERHADAP AKUMULASI UTANG MAJEMUK AKIBAT PERSEPSI RENDAH PADA BUNGA PINJAMAN ONLINE - Inaya Akbar; Reny Ramadhani; Selena Nuria Aline; Tiara Husnul Khotimah; Pinta Deniyanti Sampoerno; Debby Agustine (CV. Denasya Smart Publisher, 2026)
The rapid growth of online lending platforms in Indonesia has created new challenges in the form of systemic debt trap risks due to low financial literacy and cognitive biases. This study aims to analyze the influence of the illusion of numeracy on perceptions of online loan interest rates and its impact on the accumulation of compound debt. Using a qualitative method with a descriptive-analytical approach, data were collected through in-depth interviews with three categories of informants: mathematics students, non-mathematics students, and the general public. The findings reveal a strong phenomenon of the numeracy illusion, where informants tend to get trapped by the framing of small nominal numbers (daily interest) without converting time units or understanding the exponential nature of compound interest. Most informants use a linear thinking approach in estimating interest burdens, causing them to underestimate total financial obligations. This study concludes that critical mathematical literacy is not merely the ability to perform calculations, but rather the foundation of rationality in decision-making within the digital ecosystem. These results recommend the need for a mathematics education model that is more relevant to the contemporary financial context, as well as more transparent consumer protection policies.